Sustainable Development and The Role of Islamic and Social Banks - Abdulghani, Naser Ali (Majapahit Journal of Islamic Finance and Management, 2024)
Islamic banking is a financial system that is based on Islamic law (Sharia) and is influenced by Islamic economics. The Islamic financial system is supported by four primary pillars: the Islamic banking system, the Islamic money market, Islamic insurance (takaful), and the Islamic capital market. These systems provide alternative funding sources. Conversely, social banks are established to utilize financial services to generate a positive impact on society and the environment. Consequently, consumers perceive Islamic banks, depositors, and the broader community as having both economic and social responsibilities. The fundamental principles of the United Nations Sustainable Development Goals (SDGs) are eradicating poverty and promoting sustainable development. The parallels between Islamic and social institutions will be the focus of this investigation. The significance of the two institutions in advancing the United Nations Sustainable Development Goals (SDGs) will be underscored in this research.